Comparison of echocardiographic methods for calculating left ventricular mass in elite rugby football league athletes and the impact on chamber geometry - McGregor-Cheers, Rebecca; Forsythe, Lynsey; Cooper, Robert; Johnson, Christopher; Sculthorpe, Nicholas; Papadakis, Michael; Mill, Nathan; Daniels, Matt; Kleinnibbelink, Geert; George, Keith; Oxborough, David (Frontiers in Sports and Active Living, 2023)
Background: Recommendations for the echocardiographic assessment of left ventricular (LV) mass in the athlete suggest the use of the linear method using a two-tiered classification system (2TC). The aims of this study were to compare the linear method and the area-length (A-L) method for LV mass in elite rugby football league (RFL) athletes and to establish how differences impact the classification of LV geometry using 2TC and four-tier (4TC) classification systems.Methods: Two hundred and twenty (220) male RFL athletes aged 25 ± 5 (14-34 years) were recruited. All athletes underwent echocardiography and LV mass was calculated by the American Society of Echocardiography (ASE) corrected Linear equation (2D) and the A-L method. Left ventricular mass Index (LVMi) was used with relative wall thickness to determine geometry in the 2TC and with concentricity and LV end diastolic volume index for the 4TC.Method specific recommended cut-offs were utilised.Results: Higher values of absolute (197 ± 34 vs 181 ± 34 g; p < 0.0001) and indexed (92 ± 13 vs 85 ± 13 g/m 2 ; p < 0.0001) measures of LV mass were obtained from A-L compared to the linear method. Normal LV geometry was demonstrated in 98.2% and 80% of athletes whilst eccentric hypertrophy in 1.4% and 19.5% for linear and A-L respectively. Both methods provided 0.5% as having concentric remodelling and 0% as having concentric hypertrophy.Allocation to the 4TC resulted in 97% and 80% with normal geometry, 0% and 8.6% with eccentric dilated hypertrophy, 0% and 7.7% with eccentric non-dilated hypertrophy, 1.4% and 0.5% with concentric remodelling and 1.4% and 3% with concentric non-dilated hypertrophy for linear and A-L methods respectively. No participants had concentric dilated hypertrophy from either methods. Deleted: players 57 Deleted: V 58 Conclusion:The linear and A-L method for calculation of LV mass in RFL athletes are not interchangeable with higher values obtained using A-L method impacting on geometry classification. More athletes present with eccentric hypertrophy using 2TC and eccentric dilated/non-dilated using 4TC. Further studies should aim at establishing the association of A-L methods of LV mass and application of 4TC to the multi-factorial demographics of the athlete.